2011
DOI: 10.1007/s11999-011-1896-9
|View full text |Cite
|
Sign up to set email alerts
|

A Radiographic Classification of Massive Rotator Cuff Tear Arthritis

Abstract: Background In 1990, Hamada et al. radiographically classified massive rotator cuff tears into five grades. Walch et al. subsequently subdivided Grade 4 to reflect the presence/absence of subacromial arthritis and emphasize glenohumeral arthritis as a characteristic of Grade 4. Questions/purposes We therefore determined (1) whether patient characteristics and MRI findings differed between the grades at initial examination and final followup; (2) which factors affected progression to a higher grade; (3) whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
135
0
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(147 citation statements)
references
References 22 publications
2
135
0
10
Order By: Relevance
“…This distance, the acromiohumeral interval (AHI), measures 7-14 mm in healthy shoulders [24] and as previously mentioned if it falls below 7 mm, the probability of successful cuff repair drastically decreases [25]. Hamada et al [26] demonstrated correlation between progression of rotator cuff tear and reduction of AHI. He developed a radiographic classification of massive rotator cuff tear arthritis which divides massive rotator cuff tears into 5 grades: in Hamada Grade 1 the AHI is maintained, and narrows in Grade 2.…”
Section: Investigationsmentioning
confidence: 98%
See 2 more Smart Citations
“…This distance, the acromiohumeral interval (AHI), measures 7-14 mm in healthy shoulders [24] and as previously mentioned if it falls below 7 mm, the probability of successful cuff repair drastically decreases [25]. Hamada et al [26] demonstrated correlation between progression of rotator cuff tear and reduction of AHI. He developed a radiographic classification of massive rotator cuff tear arthritis which divides massive rotator cuff tears into 5 grades: in Hamada Grade 1 the AHI is maintained, and narrows in Grade 2.…”
Section: Investigationsmentioning
confidence: 98%
“…Acetabulization (concave deformity of the acromion undersurface) in addition to the Grade 2 narrowing is classified as Grade 3. In Grade 4, narrowing of the glenohumeral joint is added to the Grade 3 features, and Grade 5 comprises instances of humeral head collapse [26]. .…”
Section: Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fat infiltration gains importance when clinical studies find that it is associated with a worse prognosis and higher postoperative failure rates [5,15]. The degree of fatty infiltration of the supraspinatus and infraspinatus seems to be related to a worse prognosis [4,16,17]. The degree of adipose infiltration in MRI is a strong predictive factor for recurrence of postoperative rupture [9].…”
Section: Muscle Degeneration and Fat Infiltrationmentioning
confidence: 99%
“…It is also an asset in the evaluation of the competence of the coracoacromial arch [2]. The use of the Chest X-ray allowed the creation of the Hamada Radiological Classification in 1990, consisting of 5 stages that reflect the temporal evolution of rupture and a successive progression of arthropathy (Table 3) [16]. …”
Section: Diagnosismentioning
confidence: 99%